Islamic Republic of Mauritania : Second Review Under the Three-Year Extended Credit Facility Arrangement: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Mauritania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In this study, despite recovery in the aftermath of the global crisis, the following challenges faced by Mauritania are discussed: vulnerability to external shocks, an insufficiently diversified economy, weak business climate, lack of fiscal space, and high unemployment and poverty rates. The poverty reduction strategy paper (PRSP) provides a good framework. Monetary, exchange rate, and financial sector policies are explained. Debt management and the improvement of the quality of public services by fiscal reforms and private sector by the implementation of the investment code are discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet